The Role of Car Free Day in Supporting Student Entrepreneurship through Pudding Businesses in Bojonegoro - Sindy Wahyu Silvia; Saqif Bagas Baihaqi (Jurnal Kewirausahaan dan Bisnis, 2026)
Car Free Day (CFD) serves not only as a public space for recreational and social activities but also as a platform that supports economic activities, including student entrepreneurship. This study aims to analyze the role of Car Free Day in promoting student entrepreneurship through a pudding business in Bojonegoro. A qualitative descriptive approach was employed in this study. Data were collected through observations, interviews, and documentation involving students who operated pudding businesses at the Car Free Day event in Bojonegoro. The findings indicate that Car Free Day functions as an effective marketing platform while providing students with practical entrepreneurial experience, particularly in marketing, customer service, business management, and decision-making. The business development strategies implemented by the students include maintaining product quality, setting competitive prices, utilizing social media for promotion, introducing product innovations, and applying more systematic business management practices. However, several challenges were identified, including intense market competition, fluctuations in visitor numbers, limited business capital, and the short shelf life of the products. Based on the SWOT analysis, the pudding business demonstrates strong potential for further development by maximizing its strengths and opportunities while implementing appropriate strategies to address its weaknesses and external threats.   Keywords: Car Free Day, student entrepreneurship, pudding business, marketing strategy, SWOT analysis.                                                                                                 Abstrak. Car Free Day (CFD) tidak hanya berfungsi sebagai ruang publik untuk aktivitas olahraga dan sosial, tetapi juga menjadi sarana yang mendukung kegiatan ekonomi, termasuk kewirausahaan mahasiswa. Penelitian ini bertujuan untuk menganalisis peran Car Free Day dalam mendukung kewirausahaan mahasiswa melalui usaha puding di Bojonegoro. Penelitian menggunakan pendekatan kualitatif dengan metode deskriptif. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi terhadap mahasiswa yang menjalankan usaha puding di kawasan Car Free Day Bojonegoro. Hasil penelitian menunjukkan bahwa Car Free Day berperan sebagai media pemasaran yang efektif sekaligus memberikan pengalaman praktis dalam mengembangkan kemampuan kewirausahaan, seperti pemasaran, pelayanan konsumen, pengelolaan usaha, dan pengambilan keputusan. Strategi yang diterapkan meliputi peningkatan kualitas produk, penetapan harga yang kompetitif, pemanfaatan media sosial, inovasi produk, serta pengelolaan usaha yang lebih terstruktur. Kendala yang dihadapi meliputi persaingan usaha, fluktuasi jumlah pengunjung, keterbatasan modal, dan masa simpan produk yang relatif singkat. Berdasarkan analisis SWOT, usaha puding memiliki prospek yang baik untuk dikembangkan dengan memanfaatkan kekuatan dan peluang serta menerapkan strategi yang tepat dalam mengatasi kelemahan dan ancaman.   Kata Kunci: Car Free Day, kewirausahaan mahasiswa, usaha puding, strategi pemasaran, analisis SWOT.